Breeding and conservation programs with local communities - Mueller, Joaquin Pablo (2006)
Utilization strategies for genotypes that possess high levels of adaptive fitness should include breeding programs which maintain or enhance their merit and, in doing so, contribute to the economy of the communities depending on them. Issues facing such breeding programs were analyzed in five examples of breeding programs for sheep, goats and South American camelids in communities located in the Latin American Andes. Success of the breeding programs are largely related to the level of involvement of the community in the design, implementation and operation of the program. Traditional breeding procedures can be improved with the guidance of appropriately trained technical advisors. In general, such advisors are very scarce but crucial to avoid repeating mistakes and to multiply positive experiences.